2018
DOI: 10.1016/j.phymed.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

A randomised double-blind placebo-controlled pilot trial of a combined extract of sage, rosemary and melissa, traditional herbal medicines, on the enhancement of memory in normal healthy subjects, including influence of age

Abstract: This pilot study indicates that an oral preparation of SRM at the selected dose and for the period of administration is more effective than a placebo in supported verbal episodic memory in healthy subjects under 63 years of age. Short- and long- term supplementation with SRM extract merits more robust investigation as an adjunctive treatment for patients with Alzheimer's disease and in the general ageing population. The study design proved a simple cost effective trial protocol to test the efficacy of herbal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 50 publications
2
50
0
1
Order By: Relevance
“…Several randomised, double-blind, placebo-controlled, balanced-crossover trials have also demonstrated anxiolytic-like effects in humans following single doses of ethanolic extract or dried leaf powder of Lemon balm [ 3 , 4 , 5 ]; whilst chemically-characterised and combined ethanolic extracts of sage ( S. officinalis L.), rosemary ( Rosmarinus officinalis L.; accepted name: Salvia rosmarinus Schleid.) and Lemon balm improved memory in a randomised, double-blind, placebo-controlled pilot trial [ 6 ]. Similarly, single doses of dried leaf [ 7 ] and an ethanolic extract [ 8 ] of sage; containing a wide spectrum of phytochemicals, have both been shown to significantly improve mood and cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…Several randomised, double-blind, placebo-controlled, balanced-crossover trials have also demonstrated anxiolytic-like effects in humans following single doses of ethanolic extract or dried leaf powder of Lemon balm [ 3 , 4 , 5 ]; whilst chemically-characterised and combined ethanolic extracts of sage ( S. officinalis L.), rosemary ( Rosmarinus officinalis L.; accepted name: Salvia rosmarinus Schleid.) and Lemon balm improved memory in a randomised, double-blind, placebo-controlled pilot trial [ 6 ]. Similarly, single doses of dried leaf [ 7 ] and an ethanolic extract [ 8 ] of sage; containing a wide spectrum of phytochemicals, have both been shown to significantly improve mood and cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic edible plants in the mint family, used in traditional medicine through history for cognitive benefits and tested in clinical trials for cognitive effects, include sage ( S. officinalis and S. officinalis subsp. lavandulifolia ;), rosemary ( Salvia rosmarinus ; synonym: Rosmarinus officinalis ), lemon balm ( Melissa officinalis ) and mints ( Mentha species (Perry et al, ; Perry & Howes, ).…”
Section: Phytochemicals As Nutraceuticalsmentioning
confidence: 99%
“…Lamiaceae plants with centuries-old reputations for enhancing memory have been studied in RCTs and shown to enhance cognition (memory and alertness) in healthy, young and older people and to counter cognitive impairment as well as improve behavioural measures in people with AD (Perry et al, 2017) and to have positive effects on blood lipid (lowering cholesterol) and antioxidant profiles in RCTs, both of which are relevant to cognition. Rosmarinic acid, which occurs in the sub-family Nepetoidae, has shown numerous mechanistic effects relevant to cognition and AD, as reviewed previously (Williams et al, 2011) and summarised in Table 1, although its ability to cross the BBB may be limited (Perry et al, 2018). It is interesting to note that spearmint (Mentha spicata) is reported to contain the highest concentration (58%) of rosmarinic acid, followed closely by sage (S. officinalis; 37%) and rosemary (7%; Shekarchi, Hajimehdipoor, Saeidnia, Gohari, & Hamedani, 2012).…”
Section: Herbs and Spices Relevant To Cognitionmentioning
confidence: 99%
“…It has been generally recognized that traditional Chinese herbal medicines played a unique therapeutic role in the treatment of many diseases (Bhamra et al, 2017;Perry et al, 2018;Li et al, 2019). Tetramethylpyrazine (TMP), an effective component of the traditional Chinese medicine Chuanxiong Rhizoma, which has been used to treat cerebrovascular and cardiovascular diseases, pulmonary diseases and cancer (Huang et al, 2018;Shen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%